Faktor Penentu Kepercayaan Pasien Berdasarkan Karakteristik Jasa Rumah Sakit: Sebuah Systematic Literature Review - Denny Efendi; Clarissa Siswara; Charlene Siswar; Een Amalia Pratiwi; Cindy Caroline; Acep Rohendi (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Patient trust is a crucial variable in hospital management, determining clinical success, treatment adherence, and institutional loyalty. In the increasingly competitive and digitalized modern healthcare landscape, hospitals face unique challenges stemming from the inherent characteristics of healthcare services. This article presents a systematic literature review exploring the determinants of patient trust through the lens of hospital service characteristics: intangibility, inseparability, variability, and perishability. This study followed the PRISMA protocol and analyzed 150 articles published between 2010 and 2026 from Scopus, Web of Science, and Google Scholar databases. The review results indicate that assurance and empathy are the most significant service quality dimensions in mitigating perceived risk due to intangibility. Meanwhile, the quality of therapeutic communication is a key factor in managing inseparability, and standardization of operational procedures is necessary to address variability. The study also identifies the role of digital technology and the physical environment as